1997
DOI: 10.1046/j.1469-1809.1997.6130275.x
|View full text |Cite
|
Sign up to set email alerts
|

A new variant of the cytochrome P450c17 (CYP17) gene mutation in three patients with 17 α‐hydroxylase deficiency

Abstract: A new CYP17 gene abnormality was found in three Japanese patients with 17α‐hydroxylase deficiency (17OHD). These patients were children from consanguineous marriages, but from two apparently unrelated families: one patient with 46, XY karyotype, and two siblings with 46, XX and 46, XY karyotypes. They were all raised as girls and presented with amenorrhea, eunuchoid appearance and hypertension. Gene analysis revealed two base‐pair (TG) deletion in exon 5 (codons 300, 301) of the CYP17 gene. This deletion could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It is not clear why P is not routinely measured for P450c17 deficiency diagnosis, because DOC and B measurements should be performed by RIA after liquid chromatography or gas chromatography/ mass spectrometry, which is only available in a few centers, whereas P measurement is easily measured by RIA, a reliable, available, and less expensive method. A review of the literature and our data indicated that all patients with combined 17␣-hydroxylase/17,20-lyase deficiency, confirmed by CYP17 genotyping, had high basal P levels (0.7-14 ng/ml; 0.22-4.45 pmol/liter) (8,12,33,39,40,(47)(48)(49)(50)(51)(52)(53)(54)(55) compared with the respective normal values. Moreover, our patients were correctly diagnosed, even without DOC and B measurements.…”
Section: Discussionmentioning
confidence: 60%
“…It is not clear why P is not routinely measured for P450c17 deficiency diagnosis, because DOC and B measurements should be performed by RIA after liquid chromatography or gas chromatography/ mass spectrometry, which is only available in a few centers, whereas P measurement is easily measured by RIA, a reliable, available, and less expensive method. A review of the literature and our data indicated that all patients with combined 17␣-hydroxylase/17,20-lyase deficiency, confirmed by CYP17 genotyping, had high basal P levels (0.7-14 ng/ml; 0.22-4.45 pmol/liter) (8,12,33,39,40,(47)(48)(49)(50)(51)(52)(53)(54)(55) compared with the respective normal values. Moreover, our patients were correctly diagnosed, even without DOC and B measurements.…”
Section: Discussionmentioning
confidence: 60%
“…The majority of mutations of the CYP17 gene reported to date have been associated with combined 17␣-hydroxylase/17,20-lyase deficiency [9][10][11][12][13][14][15][16][17][18][19][20][21], and most muta- tions have been localized within the coding region of the CYP17 [9][10][11][12][13][14][15][16][17][18][19][20][21]40]. Studies on naturally occurring and synthetic P450c17 mutants have shown that amino acid residues, which are predicted to participate in the heme-binding region or hydrophobic active site play a crucial role, although other residues may be also important in enzyme activity [15,21,24,29].…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that the severity of clinical signs tended to be milder in cases with mutations, which retain partial enzyme activity compared to those cases, whose mutations were associated with a complete loss of enzyme activity. However, the phenotypic features appeared to be highly variable among affected individuals who had mutations that result in a complete loss of enzyme function [9][10][11][12][13][14][15][16][17][18][19][20][21]. Although the existence of isolated 17,20-lyase deficiency has been questioned, a few CYP17 mutations selectively affecting 17,20-lyase activity, including those which cause neutralization of positive charges in the redox partner-binding site have been described [21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations